Evaluation of Health Professionals and Staff Working in Private Hospitals on Knowledge of the İstanbul Convention and the Attitudes of Gender Roles - Tunç Dağdelen, Sevda Nur; Doğan, Muzaffer Berna (The Bulletin of Legal Medicine, 2024)
Objective: The objective of this research was to evaluate the understanding of İstanbul Convention among personnel and healthcare practitioners employed in private hospitals, along with examining their perspectives on gender roles.Methods: The research sample comprised 303 individuals employed at a private hospital. The study followed a descriptive-cross-sectional design. Data collection encompassed participant background information, inquiries regarding the İstanbul Convention, and the Gender Roles Attitude scale (GRAS).Results: Nurses accounted for 47.2% of the participants, and women constituted 68% of the sample. Within the subgroup endorsing Türkiye’s withdrawal from the İstanbul Convention, 85% expressed that concepts like gender identity and sexual orientation were incongruent with Turkish societal norms. The participants attained an average GRAS score of 146.61±25.68, indicative of their egalitarian outlook. Notably, GRAS scores displayed considerable variation across all demographic traits. Respondents favouring the İstanbul Convention-related queries exhibited positive GRAS scores.Conclusion: The study’s findings indicated that individuals with advanced education, females, unmarried women, nurses, those from nuclear families, individuals born in the Marmara region, those without strong political leanings, and those who pursued an egalitarian perspective exhibited elevated mean GRAS scores. As a suggestion, introducing gender role education at the primary school level and implementing in service training within healthcare institutions could be valuable.
Keywords: gender roles; gender equity; women’s rights; women